2021
DOI: 10.1021/acs.jpclett.1c00168
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Signature of Dynamic Coupling of a Strong Hydrogen Bond

Abstract: Elucidating the dynamic couplings of hydrogen bonds remains an important and challenging goal for spectroscopic studies of bulk systems, because their vibrational signatures are masked by the collective effects of the fluctuation of many hydrogen bonds. Here we utilize sizeselected infrared spectroscopy based on a tunable vacuum ultraviolet free electron laser to unmask the vibrational signatures for the dynamic couplings in neutral trimethylamine−water and trimethylamine−methanol complexes, as microscopic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Others have shown that an increase in temperature induces a frequency mismatch between the stretch fundamental and the bending overtone of bulk water, leading to a decrease in the Fermi resonance intramolecular coupling at ∼3250 cm –1 . Intramolecular coupling dominates the vibrational relaxation pathways in interfacial water. , Thus, intramolecular coupling is possibly driving the temperature-dependent spectral shifts observed in Figure a, but the exact mechanisms responsible for these spectral shifts are currently unknown. Vibrational coupling to octadecanol- d 37 vibrational modes is also possible. , Additionally, it is nontrivial to distinguish between peak intensity contributions caused by changes in hydration shell number density and structure versus changes in transition dipole moment strength as a function of temperature, further complicating the spectral interpretation. Consequently, calculations were performed that intrinsically include intra- and intermolecular coupling to study the contribution of transition dipole moments changes due to temperature for a single hydrogen-bonding configuration (Section ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that an increase in temperature induces a frequency mismatch between the stretch fundamental and the bending overtone of bulk water, leading to a decrease in the Fermi resonance intramolecular coupling at ∼3250 cm –1 . Intramolecular coupling dominates the vibrational relaxation pathways in interfacial water. , Thus, intramolecular coupling is possibly driving the temperature-dependent spectral shifts observed in Figure a, but the exact mechanisms responsible for these spectral shifts are currently unknown. Vibrational coupling to octadecanol- d 37 vibrational modes is also possible. , Additionally, it is nontrivial to distinguish between peak intensity contributions caused by changes in hydration shell number density and structure versus changes in transition dipole moment strength as a function of temperature, further complicating the spectral interpretation. Consequently, calculations were performed that intrinsically include intra- and intermolecular coupling to study the contribution of transition dipole moments changes due to temperature for a single hydrogen-bonding configuration (Section ).…”
Section: Resultsmentioning
confidence: 99%
“…Vibrational coupling to octadecanol-d 37 vibrational modes is also possible. 96,97 Additionally, it is nontrivial to distinguish between peak intensity contributions caused by changes in hydration shell number density and structure versus changes in transition dipole moment strength as a function of temperature, further complicating the spectral interpretation. Consequently, calculations were performed that intrinsically include intra-and intermolecular coupling to study the contribution of transition dipole moments changes due to temperature for a single hydrogen-bonding configuration (Section 3.2.2).…”
Section: Results Andmentioning
confidence: 99%
“…Instead, dynamic simulations are essential to reproduce its vibrational profile. [42][43][44][45][46][47] In this study, AIMD simulations are conducted by CP2K/Quickstep software. 48,49 The potential energy and atomic forces are calculated with DFT, using the BLYP functional with D3 correction, in consistency with the Gaussian calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…With the temperature calculated from the average kinetic energy, it is employed as a parameter to adjust the extent of atomic motions. [42][43][44][45][46][47] 3 | RESULTS AND DISCUSSION 3.1 | Structure and dynamics of HNO 3 (NO 3 À )…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation